Match Supervisor Reports: Developing Applications for PSSI Football Match Supervisor Reports in Medan City - Nurkadri Nurkadri; Argubi Silwan; Indra Darma Sitepu; Mawardi Nur; Taufik Akbar; Rizky Nursasongko Gunri (Budapest International Research and Critics University, 2021)
The purpose of the research is to develop a football match supervisor report in the form of an application, used for match supervisors under the auspices of the Medan City PSSI. The application is used by the PSSI match supervisor in the city of Medan to carry out all football matches in the city of Medan. The research uses development research methods adopted from the development research theory of Budiono Saputro. The implementation of the research uses a preliminary study step, namely library research, analyzing needs, and designing applications according to the match supervisor's report. The next step is making application products, validating to product revision experts, revision individual trials, and group trials. The results of material expert validation are 82.45% good category, media expert validation results are 81.01% good category. The application assessment from the expert showed that expert I was 87.47% very good category, expert II was 86.89% very good category. The results of individual trials showed 86.85% easy assessment using the very good category, the overall assessment was 87.75% in the very good category. The results of the match supervisor's assessment were 85.46% in the aspect of using the very good category, and 85.76% in the overall aspect of the very good category. The conclusions of the research on the development of the match supervisor report with the application, based on the assessment data of the Medan City PSSI Match Supervisor on several aspects that have been developed have been suitable for use with some suggestions and inputs for improvement, which can then be used as the final product of the research. It is hoped that further research will be carried out on other aspects for a more perfect application of the developed match supervisor report.